The Pictorial Personality Traits Quesionnaire – presentation of the questionnaire - Rogoza, Marta (Studia Psychologica: Theoria et praxis, 2019)
Currently, it is assumed that the personality structure, including the period of the childhood, could be described through the means of the Big Five traits. A big challenge, however, is to select such a measure, which would take into account the development of reading, concentration, and other cognitive aspects, which are still developing in younger children. Therefore, the aim of the current study if to demonstrate that the Pictorial Personality Traits Questionnaire for Children (PPTQ-C), which is a questionnaire designed to capture five basic personality traits, that is: extraversion, neuroticism, openness, conscientiousness, and agreeableness during the late childhood period. The PPTQ-C could be deemed as a valid and reliable tool, which covers the existing lack in such tools, especially for children aged between 7 and 10 years. The PPTQ-C combines the best features of questionnaire and non-questionnaire methods of assessment and is adjusted to the cognitive development of children.